PSII-38 The effect of clitoral stimulation post fixed-time insemination in Bos indicus beef cattle. (5th December 2019) - Filho, Ramiro Oliveira; Mello, Gustavo Azevedo de; Pereira, Victor Mendonça; Vasconcelos, Jose Luiz Moraes; Cooke, Reinaldo F; Pohler, Ky
Abstract: The objective of this experiment was to evaluate the effect of clitoral stimulation post-insemination on pregnancy rates in Bos indicus beef cattle. A total of 1186 multiparous Nelore cows were assigned to an estradiol-based estrus synchronization + timed-AI protocol (FTAI, d 0), and randomly assigned to receive either 2 to 5 seconds of clitoral stimulation or no clitoral stimulation after artificial insemination. Estrus expression prior to AI was evaluated based on patch activation (estrus, ≥ 50% activated; no estrus, < 50% activated) using Estrotect Heat Detector and chute exit velocity after AI was evaluated. Individual exit score was calculated within each group by dividing exit velocity into quintiles and assigning cows with a score from 1 to 5 (1 = slowest; 5 = fastest). Artificial insemination was performed by 7 different technicians. Pregnancy diagnosis was performed 30 days after FTAI via transrectal ultrasonography. Overall pregnancy rate at day 30 was 46.0% (545/1186). Clitoral stimulation had no beneficial effect (P = 0.42) on pregnancy rate of multiparous cows when compared to those not stimulated (47.5% ± 4.6 vs. 44.3% ± 4.6). Cows that expressed heat at d 0 (n = 602) had a greater (P < 0.01) pregnancy rate compared to no heat expression (37.6% ± 4.7 vs. 60.6% ± 4.6), but no effect of the clitoral stimulation was observed on pregnancy rate in cows that did or did not express heat (P > 0.05). Furthermore, clitoral stimulation did not affect exit score (P = 0.67) of cows after FTAI. No effect of the technician was observed on pregnancy rate when clitoral stimulation was applied or not (P = 0.21). In summary, clitoral stimulation was not a useful managerial tool to improve pregnancy rate in multiparous Bos indicus cows submitted to FTAI using estradiol-based protocols.